2009
DOI: 10.1167/9.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational length, gender, postnatal age, and birth order on visual contrast sensitivity in infants

Abstract: To investigate effects of visual experience versus preprogrammed mechanisms on visual development, we used multiple regression analysis to determine the extent to which a variety of variables (that differ in the extent to which they are tied to visual experience) predict luminance and chromatic (red/green) contrast sensitivity (CS), which are mediated by the magnocellular (M) and parvocellular (P) subcortical pathways, respectively. Our variables included gestational length (GL), birth weight (BW), gender, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 168 publications
(179 reference statements)
4
18
0
Order By: Relevance
“…S1b in the Supplemental Material). This finding is consistent with studies that have demonstrated that the rate at which contrast sensitivity develops slows by age 6 months (Dobkins, Bosworth, & McCleery, 2009), and that luminance contrast sensitivity, in particular, is more closely tied to preprogrammed mechanisms than to visual experience (Bosworth & Dobkins, 2009). …”
Section: Resultssupporting
confidence: 91%
“…S1b in the Supplemental Material). This finding is consistent with studies that have demonstrated that the rate at which contrast sensitivity develops slows by age 6 months (Dobkins, Bosworth, & McCleery, 2009), and that luminance contrast sensitivity, in particular, is more closely tied to preprogrammed mechanisms than to visual experience (Bosworth & Dobkins, 2009). …”
Section: Resultssupporting
confidence: 91%
“…Numerous studies have investigated preterm infants with the goal of determining whether development of different abilities is supported by experience or neural maturation. In contrast to the current study and the large literature documenting the developmental difficulties associated with prematurity, many of these studies have concluded that preterm infants are relatively unimpaired or even accelerated in their development(e.g., [35, 36, 37]). It may be that relatively low-level, early developing abilities are not disrupted by premature birth, but the disruption of foundational developmental mechanisms, as reported here, has developmental consequences that emerge later in life or in different domains.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the P pathway is sensitive to high spatial frequency patterns, low temporal frequencies, and shows sustained responses to stimuli (Breitmeyer and Ganz, 1976; Lennie, 1980; Kaplan and Shapley, 1986; Livingstone and Hubel, 1987; Bassi and Lehmkuhle, 1990). Most relevant to the current study, the M pathway exhibits high contrast sensitivity to luminance (light/dark) patterns, and low contrast sensitivity to chromatic (red/green) patterns; conversely, the P pathway exhibits high contrast sensitivity to chromatic (red/green) patterns and low contrast sensitivity to luminance (light/dark) patterns (Lee et al, 1990; Shapley, 1990; Smith et al, 1995; Dobkins et al, 2009). In terms of cortical projections, the M pathway provides input to both the dorsal processing stream (the “where” system, which processes motion and space information) and the ventral processing stream (the “what” system, which processes object information) (Maunsell et al, 1990; Thiele et al, 2001), while the P pathway provides input primarily to the ventral processing stream.…”
Section: Introductionmentioning
confidence: 82%